2007
DOI: 10.1002/dmrr.757
|View full text |Cite
|
Sign up to set email alerts
|

Tissue factor activities of streptozotocin induced diabetic rat tissues and the effect of peanut consumption

Abstract: Elevated TF activity in diabetic rat tissues, may contribute to the increased risk of atherothrombotic disease that accompanies the diabetic complications whereas the decreased brain TF activity may be due to a different haemostatic mechanism to protect this vital organ from the diabetic status. The decreased TF activity of peanut given diabetic rat tissues might protect these tissues from the risk of thrombosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 47 publications
(60 reference statements)
1
20
0
2
Order By: Relevance
“…19 It could also be the case in our model, since a marked increased level of IL-1β in STZ-induced diabetic rats was observed.…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…19 It could also be the case in our model, since a marked increased level of IL-1β in STZ-induced diabetic rats was observed.…”
Section: Discussionmentioning
confidence: 50%
“…It is necessary to mention that TF is recognised as an essential initiator of thrombin generation and coagulation which may be involved in thrombus propagation at the site of vascular injury. 18,19 The mechanism of TF increase in diabetes may be related to the formation of advanced glycation end products and reactive oxygen species, which activate NFκB leading to TF production. 20 Hyperglycaemia impairs fibrinolytic activity on the surface of endothelial cells and decreases plasma fibrinolytic potential.…”
Section: Discussionmentioning
confidence: 99%
“…Low levels of TF lead to alveolar hemorrhage, potentiating murine acute lung injury and oxidative stress (Bastarache et al, 2012). Emekli-Alturfan et al (2007) indicated a decrease in lung TF activity in STZ-treated rat. A similar result was also obtained in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…It is not actively found in the blood but it is the cell component of the membranes (48). It has been shown that some tissues and fluids of the body have TF activities (49)(50)(51)(52)(53)(54). Thrombotic and fibrinolytic mechanisms are activated after burn injury, with the extent of activation correlated to the severity of the thermal injury (5).…”
Section: Discussionmentioning
confidence: 99%